Integration of Circular Economy Approaches and Community Participation in Waste Management Based on Campus-Village Partnerships - Arie Sujito; Nefa Wahyuning Anggraini (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2025)
Urbanization and rapid population growth in Yogyakarta have significantly increased waste production, ultimately exacerbating the environmental crisis due to the failure of conventional disposal-based management systems. This study explores a circular economy approach in waste management based on a campus-village partnership by highlighting the collaboration between Gadjah Mada University and Sinduadi Village. Using a qualitative approach, this research analyzes the dynamics of waste management, the challenges of policy implementation, and the role of the community in realizing a more sustainable system. The research findings indicate that the implementation of a circular economy in waste management faces challenges such as limited infrastructure, minimal community participation, and lack of coordination among stakeholders. However, with the integration of the ReSOLVE concept and the Quadruple Helix approach, collaboration between academics, government, industry, and society can drive innovation in waste management, resource optimization, and environmental awareness. Campus-village partnerships play a strategic role in building circular-based business models that not only address waste issues but also create local economic opportunities. This research emphasizes the importance of synergy between regulatory policies, monetary incentives, and technological innovations in strengthening the circular economy ecosystem. The implications of this study highlight that the success of transforming the waste management system depends on the sustainability of cross-sector collaboration and active community participation in holistically applying circular economy principles. Keywords. Circular Economy, Waste Management, Campus-Village Partnership, Environmental Governance, Community Participation